Phosphorus and short-chain fatty acids recovery from waste activated sludge by anaerobic fermentation: Effect of acid or alkali pretreatment. (September 2017) - Wu, Liang; Zhang, Cheng; Hu, Hui; Liu, Jianyong; Duan, Tengfei; Luo, Jinghuan; Qian, Guangren
Highlights: P and SCFAs recovery from WAS by AF with acid or alkali pretreatment was proposed. Both acid and alkali pretreatment effectively enhanced SCFAs production by AF. Alkali pretreatment enhanced conversion of organic P to inorganic P. Acid pretreatment was more beneficial for inorganic P release into solution. Acid pretreatment is preferred for simultaneous recovery of P and SCFAs by AF. Abstract: Waste activated sludge (WAS) was pretreated by acid or alkali to enhance the anaerobic fermentation (AF) for phosphorus (P) and short-chain fatty acids (SCFAs) release into the liquid simultaneously. With acid pretreatment, the released total P concentration achieved 120 mg/L, which was 71.4% higher than that with alkali pretreatment. In addition, alkali pretreatment enhanced organic P release with about 35.3% of organic P in the solid being converted to inorganic P, while little had changed with acid pretreatment. The results also showed that acid and alkali pretreatment enhanced SCFAs production by 15.3 and 12.5 times, respectively. Acid pretreatment could be preferred for simultaneous recovery of P and SCFAs by AF.